A Comparasion of Laboratory and Cardiopulmonary Effects of Desflurane, Detomidine and Medetomidine Anaesthetic Combinations in Horses - Erol, Hanifi; Arıcan, Mustafa (Acta Scientiae Veterinariae, 2017)
Background: Equine anesthesia morbidity and mortality rates are greater than in other domestic animals because of hypotension and hypoventilation. The important features desired in general anesthesia for horses are a rapid effect, rapid emergence and balanced anesthesia. The long duration of action of currently used anesthetic agents cause various complications in horses. The aim of the present study was to compare the clinical effects of combination of the anesthetics desflurane, detomidine and medetomidine in horses. Materials, Methods & Results: Eight healthy mixed-breed horses (four males and four females) with weighing 275 ± 56 kg [mean ± standard deviation (SD)] and aged 6.8 ± 5 years [(mean ± SD)] were used for this study. The horses were placed into one of four groups: group I (detomidine-desflurane), group II (detomidine-desflurane-atipamezole), group III (medetomidinedesflurane), or group IV (medetomidine-desflurane-atipamezole). Horses were rested for 15 days before each group starts to study. Intravenous detomidine (25 µg/kg) was used for premedication in groups I and II, and intravenous medetomidine (7 µg/ kg) was used for premedication in groups III and IV. Ketamine hydrocholoride (2 mg/kg) and midazolam (0.03 mg/kg) were intravenously administered in the same syringe to induce anesthesia. After induction of anesthesia, horses were placed in the left lateral recumbent position, and the trachea was intubated with a cuffed endotracheal tube with an internal diameter of 28 mm. The endotracheal tube was attached to a large animal circle breathing system anesthesia machine, and anesthesia was maintained with desflurane for 90 min. The initial dosage of desflurane was 14% + 4 L O2/min, and was reduced by 2% every 10 min over the first 30 min of anesthesia. After 30 min, the desflurane dose was changed to 8% + 4 L, which was maintained until the end of anesthesia (90 min). After 90 min, the administration of desflurane was discontinued, and all animals were supported by O2, with groups II and IV receiving 0.06 mg/kg atipamezole in addition to oxygen. Anaesthetic action times, hematological parameters, blood gas levels, electrolyte levels, biochemical values, electrocardiography values and end-tidal carbon dioxide volume were measured before, during, at the end of, and 24 h after anesthesia. Discussion: In this study, medetomidine (7 µg/kg) and detomidine (25 µg/kg) were intravenously administered, which was adequate and suitable for sedating horses. At the end of anesthesia, 0.06 mg/kg atipamezole was intravenously administered in groups II and IV. However, atipamezole did not affect the clinical parameters. Stress, excitement, fear, catecholamine exchange in blood circulation, hyperglycemia, and hypoxia can all cause changes in venous blood parameters. These are potential reasons for the changes in venous blood parameters (i.e., WBC and Hb) observed at the beginning of and during anesthesia in the present study. During and after the anesthetic period, serum biochemical values can be different from baseline values. They are dependent on the effects of anesthetic agents. During anesthesia, the decrease and increase of biochemical values stabilize the changes in the enzyme system that develops because of the effects of anesthetic agents. In the present study, it was considered that the changes in the biochemical values aimed to stabilize the changes induced by anesthesia. Regarding the electrolyte parameters evaluated in the study, there was a statistical difference detected in Na values between 90 min after induction of anesthesia and 24 h after induction of anesthesia in group IV. However, in previous studies, the changes in Na values did not influence the cardiac pressure during general anesthesia. In our study, significant changes were not seen in any electrolyte parameters except Na, and atrioventricular block was not detected in ECG traces. Generally, decreased ETCO2 levels are evidence of lung perfusion deficiency. It depends on the effects of anesthetic agents on the cardiopulmonary, cardiovascular, and respiratory systems. In particular, the higher pressure and dose of desflurane supress respiratory system. Oxygen supplementation in general anesthesia increases respiratory rate, but a-2 agonists and ketamine-midazolam effects can eliminate the increasing respiratory rate in general anesthesia.